A CHIOTE POTTERY WORKSHOP OF THE ROMAN PERIOD: in memoriam Vivien Swan - Opaiţ, Andrei; Tsaravopoulos, Aris (Rei Cretariae Romanae Fautorum Acta, 2024)
The intense rescue excavations carried out by the archaeologists of the Greek Archaeological Service from the early 1980’s increased our knowledge of the various limits of the ancient town of Chios and of its commercial and industrial activity. The focus of this paper concerns the southern manufacturing area that specialised in making amphorae during the early Roman period.